REJESTR DŁUŻNIKÓW NIEWYPŁACALNYCH - Palmirski, Tomasz (Zeszyty Prawnicze, 2017)
Register of Insolvent Debtors Summary The register of insolvent debtors is a complete novelty in the Polish legal system. Contrary to its name, not all insolvent entities are to be entered in it, but only those which comply with the prerequisites determined in art. 55 or art. 56 National Court Register. The article herewith, resulting from the author’s experience as a judge is designed to be a wrap-up of hitherto notions expressed in the doctrine and jurisdiction regarding the application of the provisions of the National Court Register Act which reguletes influence the functioning of the Register of Insolvent Debtors.